2011
DOI: 10.1186/1471-2334-11-176
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of HBV infection in the cohort of IDPs of war against terrorism in Malakand Division of Northern Pakistan

Abstract: BackgroundHepatitis B is an important public health problem in the Pakistani population and is the major cause of chronic hepatitis, cirrhosis, fibrosis and hepatocellular carcinoma. High prevalence of HBV infections has been observed especially in areas of low economic status. In spite of effective immunization programs, no significant change has been observed in the epidemiology of HBV in the rural areas of Pakistan (~67.5% of the total population) mainly due to lack of interest from government authorities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 15 publications
3
36
1
Order By: Relevance
“…Nearly similar results have been reported earlier from other parts of Pakistan as high prevalence of HBV was observed in male gender (78.04%) as compared to female gender (21.95%) (Khan et al, 2011;Shazi and Abbas, 2006). Likewise in the neighboring countries the prevalence rate of HBV infection is significantly high in males as compared to female (Zhang et al, 2011;Zali et al, 1996).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nearly similar results have been reported earlier from other parts of Pakistan as high prevalence of HBV was observed in male gender (78.04%) as compared to female gender (21.95%) (Khan et al, 2011;Shazi and Abbas, 2006). Likewise in the neighboring countries the prevalence rate of HBV infection is significantly high in males as compared to female (Zhang et al, 2011;Zali et al, 1996).…”
Section: Discussionsupporting
confidence: 90%
“…We do not have any data on sharing of personal items, on house hold contact, on dental medical and medical surgeries. Recently Khan et al (2011) noted that the aforementioned risk factors that were strongly correlated with HBV infection in general populace of Pakistan (Khan et al, 2011). The findings of this study suggest an alarming high rate of HBV infection among the conflict-affected people.…”
Section: Discussionmentioning
confidence: 78%
“…This study also indicated the potential risk factors for HBV infection in the people from war-affected areas [8]. Moreover, genotype C of HBV was found to be the dominant genotype that was prevalent at 38.8% in the Pashtun population [9].…”
Section: Resultsmentioning
confidence: 97%
“…In addition, war has led to the restriction of access to basic health services, such as vaccination, safe injections, and obstetric health care. Also, a high prevalence of HBV among people displaced by war has been reported [Khan et al, ]. Temporary immigration out of war‐affected could also have a significant impact on the epidemiological profile of infectious agents like HBV.…”
Section: Discussionmentioning
confidence: 99%